Integrated education through lectures, case scenarios, and peer groups enhances health cadres’ knowledge and attitudes - Akhmadi; Lismidiati, Wiwin; Anita, Ayu; Nur, Muhammad; Amir, Fadjrianty Fadhilah; Zakaria, Muhamad Abi (BKM Public Health and Community Medicine, 2025)
Purpose: Stunting is a serious global issue characterized by children's height not being proportional to their age. The high prevalence of stunting is caused by factors such as chronic malnutrition, recurrent infections, and a lack of psychosocial stimulation during the first 1,000 days of life. This study aims to evaluate the effectiveness of integrated education in improving health cadres' knowledge and attitudes regarding stunting prevention in Panggungharjo Village. Methods: The method used was quantitative with a quasi-experimental design without a control group, involving 14 health cadres for toddlers as the sample. Data were analyzed using a paired t-test. Results: The results showed a significant improvement in knowledge between the pre-test and post-test (p < 0.05). However, the attitude assessment results indicated a p-value of 0.087, suggesting that the attitude improvement from the pre-test to the post-test was not statistically significant (p > 0.05). Conclusion: This study concludes that integrated education involving lectures, case scenarios, and peer group methods is efficacious in improving health cadres' knowledge about stunting prevention. However, it has not yet proven effective in enhancing cadres' attitudes. Therefore, additional strategies are needed to improve the attitudes of health cadres. The implementation of similar educational methods in other communities is expected to contribute to a sustainable reduction in stunting prevalence.